Magnetic Resonance Imaging Features of Cervical Spine Intraspinal Extradural Synovial Cysts. Issue 4 (November 2019) - Mak, Davina; Vidoni, Alessandro; James, Steven; Choksey, Munchi; Beale, David; Botchu, Rajesh
Spinal synovial cysts are relatively uncommon and are most frequently found in the lumbar spine and rarely in the cervical spine. Intraspinal extradural cervical synovial cysts can occur and potentially cause cord/nerve root compression with symptoms of myelopathy/radiculopathy; however, most are asymptomatic and incidental findings. We conducted a literature review and present, to our knowledge, the largest imaging case series and describe the magnetic resonance imaging features of cervical synovial cysts.